The Figures of Orants in the Rotunda in Thessaloniki: Between Ideal and Individual - Obraztsova, Kseniia B. (Actual Problems of Theory and History of Art, 2019)
The article is dedicated to the representations of orants in the Rotunda in Thessaloniki. They are usually interpreted as martyrs, but there is another opinion, which claims that the orants depict donators.With the help of the iconographical analogies and hagiographical sources, the article defends the traditional view on the images. A further point of concern are the artistic features of the mosaics with the focus on treatment of faces of the orants. Being highly individualized, they do give an impression of portraits — an uncommontendency in Early Christian representations of saints, where, instead of stressing the individual characteristics of a person that had once lived, the emphasis tends to be on the over individual afterlife. The faces of martyrs in Rotunda look very close to each other, but in the same time, they demonstrate an extraordinary diversity of characteristics that should be understood as variations on the general type of image. The unity ofthe faces is determined by conventional and abstract artistic means, while a broad set of artistic principles are shaping the inner character and enriching the general scheme. The personal attitude in the representation of saints enables us to compare the images of the Rotunda with the contemporary sculpture portraits. However, a similar tendency towards a generalized image can be traced in the true portraiture as well. Through the comparison of the portrayals of saints and of living persons, the article attempts to reveal the attitude towards personality in the period under discussion.